Crop Water Requirement in a Sub-Watershed of Mahabubnagar District of Telangana for Kharif Rice Cultivation using Geospatial Techniques - Choudhury, Aloshree; Mahammood, Vazeer; Rao, K. H. V. Durga (Engineering And Technology Journal, 2023)
In a sub-watershed of the Mahabubnagar district of Telangana state, India, the paper focuses on estimating the irrigation water requirements of paddy crops for the kharif season from 2019 to 2021. The Random Forest Classifier in Google Earth Engine has used Sentinel-2 to determine the area that is being used for paddy cultivation. Using the Hargreaves model, potential evapotranspiration (ETο) has been calculated. The crop coefficient (Kc) for paddy and potential evapotranspiration (ETο) were used to calculate the crop’s water requirements (Etc). Utilizing gridded rainfall data from the CHRS (Center for Hydrometeorology and Remote Sensing) - PERSIANN-Cloud Classification System (PERSIANN-CCS 4km x 4km), effective rainfall was calculated. To calculate the amount of irrigation water needed, effective rainfall and crop water needs were taken into consideration. Net irrigation water need was calculated by assuming 30% losses. The amount of water needed for paddy is calculated by multiplying the paddy cropped area by the net irrigation water requirement.